Vancomycin and daptomycin minimum inhibitory concentration distribution and occurrence of heteroresistance among methicillin-resistant Staphylococcus aureus blood isolates in Turkey - KORTEN, VOLKAN (BIOMED CENTRAL LTD, 2013)
Background: The aim of this study was to determine the distribution of vancomycin and daptomycin MICs among methicillin-resistant Staphylococcus aureus (MRSA) blood isolates, the prevalence of heterogeneous vancomycin-intermediate S. aureus (hVISA) and the relationship between hVISA and vancomycin MIC values. Methods: A total of 175 MRSA blood isolates were collected from seven university hospitals in Turkey. All isolates were tested for susceptibility to vancomycin and daptomycin by reference broth microdilution (BMD) and by standard Etest method. BMD test was performed according to CLSI guidelines and Etest was performed according to the instructions of the manufacturer. All isolates were screened for the presence of the hVISA by using macro Etest (MET) and population analysis profile-area under the curve (PAP-AUC) methods. Results: The vancomycin MIC50, MIC90 and MIC ranges were 1, 2, and 0.5-2 mu g/ml, respectively, by both of BMD and Etest. The daptomycin MIC50, MIC90 and MIC ranges were 0.5, 1 and 0.125 -1 mu g/ml by BMD and 0.25, 0.5 and 0.06-1 mu g/ml by Etest, respectively. The vancomycin MIC for 40.6% (71/175) of the MRSA isolates tested was >1 mu g/ml by BMD. No vancomycin and daptomycin resistance was found among MRSA isolates. Percent agreement of Etest MICs with BMD MICs within +/- 1 doubling dilution was 100% and 73.1% for vancomycin and daptomycin, respectively. The prevalence of hVISA among MRSA blood isolates was 13.7% (24/175) by PAP-AUC method. MET identified only 14 of the hVISA strains (sensitivity, 58.3%), and there were 12 strains identified as hVISA that were not subsequently confirmed by PAP-AUC (specificity, 92.1%). Conclusions: Agreement between BMD and Etest MICs is high both for vancomycin and daptomycin. Daptomycin was found to be highly active against MRSA isolates including hVISA. A considerable number of isolates are determined as hVISA among blood isolates. As it is impractical to use the reference method (PAP-AUC) for large numbers of isolates, laboratory methods for rapid and accurate identification of hVISA need to be developed.
Keywords: Vancomycin; Daptomycin; MIC; Heteroresistance; MRSA; Blood isolates; REDUCED SUSCEPTIBILITY; MIC CREEP; INTERMEDIATE; BACTEREMIA; UK; GLYCOPEPTIDES; INFECTIONS; FAILURE; STRAINS; TRENDS